Photothermal response of hollow gold nanoshell to laser irradiation: Continuous wave, short and ultrashort pulse. (October 2015) - Hatef, Ali; Fortin-Deschênes, Simon; Boulais, Etienne; Lesage, Frédéric; Meunier, Michel
Highlights: Study of the photothermal response of gold nanoshell for biomedical applications. Continuous-wave (CW), short (nanosecond) and ultrashort (femtosecond) pulse laser. The influence of laser intensity on temperature at the particle/water interface. Abstract: This paper is to investigate numerically the photothermal response of the most common size of gold nanoshell (AuNS) in an aqueous medium for biomedical applications. Three types of laser light irradiate the particle; a continuous-wave (CW), short (nanosecond) and ultrashort (femtosecond) pulse laser. The spatiotemporal evolution of the temperature profile inside and around the AuNS is computed using a numerical framework based on the finite element method (FEM). For CW and nanosecond (ns) pulse laser where the AuNS's electrons and lattice are at thermal equilibrium, the ordinary heat diffusion equation is used to describe the heat transfer to the surrounding water. For femtosecond (fs) pulse laser, due to the inexistence of the thermal equilibrium, a two-temperature model (TTM) is used to describe the heat transfer processes occurring in the AuNS and the normal heat diffusion equation is used for the heat flux calculation at the particle/water interface. For each case, the influence of laser intensity on the maximum temperature reached at the particle/water interface is studied. The aim of this study is to provide a description for the fundamentals of heat release of AuNSs and useful insights for the development of these particles for biomedical applications such as drug delivery, photothermal cancer therapy and optoporation of cells.